Standardizing leucocyte PNH clone detection: An international study. Issue 5 (9th April 2014) - Fletcher, Matthew; Sutherland, D. Robert; Whitby, Liam; Whitby, Alison; Richards, Stephen J.; Acton, Erica; Keeney, Michael; Borowitz, Michael; Illingworth, Andrea; Reilly, John T.; Barnett, David
<x xml:space="preserve">Abstract</x> Background Consensus and Practical Guidelines for robust high‐sensitivity detection of glycophosphatidylinostitol‐deficient structures on red blood cells and white blood cells in paroxysmal nocturnal hemoglobinuria (PNH) were recently published. Methods UK NEQAS LI issued three stabilized samples manufactured to contain no PNH cells (normal), approximately 0.1% and 8% PNH leucocyte populations, together with instrument‐specific Standard Operating Procedures (SOPs) and pretitered antibody cocktails to 19 international laboratories experienced in PNH testing. Samples were tested using both standardized protocol/reagents and in‐house protocols. Additionally, samples were issued to all participants in the full PNH External Quality Assessment (EQA) programs. Results Expert laboratory results showed no difference in PNH clone detection rates when using standardized and their "in‐house" methods, though lower variation around the median was found for the standardized approach compared to in‐house methods. Neutrophil analysis of the sample containing an 8% PNH population, for example, showed an interquartile range of 0.48% with the standardized approach compared with 1.29% for in‐house methods. Results from the full EQA group showed the greatest variation with an interquartile range of 1.7% and this was demonstrated to be significantly different (P < 0.001) to the standardized cohort. Conclusions The results not only demonstrate that stabilized whole PNH blood samples are suitable for use with currently recommended high‐sensitivity reagent cocktails/protocols but also highlight the importance of using carefully selected conjugates alongside the standardized protocols. While much more variation was seen among the full UK NEQAS LI EQA group, the standardized approach lead to reduced variation around the median even for the experienced laboratories. © 2014 International Clinical Cytometry Society